Effect of short-term cold-water immersion on muscle pain sensitivity in elite track cyclists. (July 2018) - Klich, Sebastian; Krymski, Igor; Michalik, Kamil; Kawczyński, Adam
Abstract: Objective: To determine the effect of short-term cold-water immersion (CWI) on muscle pain sensitivity after maximal anaerobic power training in track cyclists. Design: Repeated measures. Setting: University Laboratory. Participants: 12 elite sprint track cyclists (age 24, 75 ± 4, 23 years). Main outcome measures: PPT measurements were made on dominant lower extremity (right) in 20 reference points, including anterior thigh muscles, posterior thigh muscles and posterior cuff muscles. PPT levels were measured: 1) before workout, 2) immediately after workout, but before CWI 3) 1 h after CWI and 4) 12 h after CWI. Mean PPT values for each muscle group per participant were calculated for further statistical analysis. Results: The average PPT for anterior thigh muscles decreased significantly after effort (p = 0.001) and increased significantly 1 h after CWI (p = 0.048). In posterior thigh muscles PPT decreased significantly after effort (p = 0.014) and increased significantly 1 h and 12 h after CWI (p = 0.045 and p = 0.25 respectively). However, in posterior cuff muscles PPT decreased only after effort (p = 0.001). Conclusions: Short-term repeated sprint exercise appears to affect PPT in track cyclists. This study have reported that CWI in 5 °C for 5 min have had a beneficial effect in minimizing PPT 1 h post repeated maximal sprint training. Highlights: Pressure Pain Threshold (PPT) of lower extremity, in elite track cyclist, was measured. PPT increased after maximal sprints trials and decreased after cold-water immersion (CWI). PPT in back thigh muscles decreased only significant after 12 h of CWI. No significant changes in back shin muscles were observed after CWI.